Thermal behaviour of TEGMMA copolymers obtained by photopolymerization using iron complexes - Rigoli, Isabel Cristina; Cavalheiro, Carla Cristina Schmitt; Ramos, Luiz Antonio; Neumann, Miguel Guillermo; Cavalheiro, Éder Tadeu Gomes (Eclética Química, 2007)
Copolymers of methyl methacrylate (MMA) and triethyleneglycol dimethacrylate (TEGDMA) obtained by photoinitiated polymerization using Fe(III) complexes were submitted to thermogravimetry (TGA) under dynamic air atmosphere and N 2 , and differential scanning calorimetric analysis (DSC). Thermal events were observed only between 90 - 110 °C. Glass transitions were observed at ca. 100 °C, followed by an exothermic peak at 170 °C. The exothermic peak was assigned to a thermal curing process due to the presence of unreacted vinyl groups of the monomers. DSC revealed to be a useful tool to evaluate the curing completeness in this kind of material, using small amounts of sample in relatively short time.